Advanced Study on Economic Structural Change and Economic Growth in Egypt - Elshamy, Hany M. (Insights into Economics and Management Vol. 10, 2021)
This paper reasons about the economic structural change and economic growth in Egypt amid the period 1983-2014. This paper utilizes the procedure of Vries et a. 2014. The paper utilizes the novel Penn World Table (PWT) adaptation 9 information base to cover the period somewhere around 1983 and 2014. It is found that there were economic structure changes amid the period 1983-2014 as the significance of the agriculture sector declined over the time, the significance of the industry sector expanded since to 1990, and the significance of the service sector expanded following 2000. Additionally, this exploration affirms that there is a solid connection (with a coefficient correlation of 85.11 percent) between the two series of employment and GDP growth rates. As indicated by the labour productivity deterioration the inside impact was constantly more noteworthy than the aggregate reallocation impact However, in the event that we take a gander at the two parts of the aggregate reallocation impact, unmistakably the dynamic reallocation impact has a major part in deciding the total productivity growth. Therefore, another strategy ought to be intended to support the voluntary labour movement crosswise over sectors and areas in Egypt.